If it's not what You are looking for type in the equation solver your own equation and let us solve it.
9x+21=6x+63
We move all terms to the left:
9x+21-(6x+63)=0
We get rid of parentheses
9x-6x-63+21=0
We add all the numbers together, and all the variables
3x-42=0
We move all terms containing x to the left, all other terms to the right
3x=42
x=42/3
x=14
| 2q-74=2 | | 1.045^t=2 | | 2x*x-9x+6=0 | | x/3+3x-4=10 | | 3q*q-118.5q+328.5=0 | | 2x=40/21 | | 3x÷7=49 | | 3q*q*q-118.5q+328.5=0 | | 7(2x-2)=-14x-14 | | 1=c/6 | | 2(1-2.5x)+5x=2 | | 2(1-2.5x)+5x=1 | | 6x+22=7x+16 | | 7=2y+9 | | 7x-21=5x+99 | | 8x+6=7x+24 | | 9/8a=19 | | 12+7.5n=6+7.9n | | (7x-27)+(3x+29)=180 | | 91=-7(3a–1) | | 3x-23=2x-12 | | 3y-9=+y | | 20a-13=20× | | 5=r/20 | | A=(1,3,5)xA | | -8(35x+40)=-16(1+17x+11x | | 4+-3j=10 | | 2x+18=6x+8 | | 5(n+8)=39+5n | | 8a+2=9 | | .4^x=1.6 | | 14=4z-2 |